2016
DOI: 10.18203/2320-6012.ijrms20162285
|View full text |Cite
|
Sign up to set email alerts
|

Preterm premature rupture of membranes: correlates and pregnancy outcome in a tertiary care setting

Abstract: INTRODUCTIONPrelabour membrane rupture before 37 weeks of gestation is referred to as preterm premature rupture of membranes (PPROM). Incidence of PPROM is about 2% of all pregnancies. 1 The consequences of PPROM for the neonate fall into three major overlapping categories. The first is the significant neonatal morbidity and mortality associated with prematurity. Secondly the complications during labor and delivery increase the risk for neonatal resuscitation and thirdly infection. The relative contributions o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 3 publications
2
13
3
Order By: Relevance
“…The prevalence of PPROM among women admitted at the Bamenda Regional Hospital was 4.91% and it accounted for one-third of all preterm births. Our prevalence is close to 4.1% reported by Abouseif et al [11] in Egypt and to 4% reported by Rajan et al [7] in India. Our prevalence is higher than the 3.3% reported by Okeke et al [10] in Nigeria, the 2.8% reported by Bouvier et al [8] in Canada and that reported by Hackenhaar et al [9] in Brazil of 3.1%.…”
Section: Prevalence Of Preterm Premature Rupture Of Membranessupporting
confidence: 86%
See 1 more Smart Citation
“…The prevalence of PPROM among women admitted at the Bamenda Regional Hospital was 4.91% and it accounted for one-third of all preterm births. Our prevalence is close to 4.1% reported by Abouseif et al [11] in Egypt and to 4% reported by Rajan et al [7] in India. Our prevalence is higher than the 3.3% reported by Okeke et al [10] in Nigeria, the 2.8% reported by Bouvier et al [8] in Canada and that reported by Hackenhaar et al [9] in Brazil of 3.1%.…”
Section: Prevalence Of Preterm Premature Rupture Of Membranessupporting
confidence: 86%
“…Preterm PROM occurs in approximately 3% of all pregnancies and causes about one third of preterm births [2]. The prevalence of PPROM ranges from 2.2% -4% in India [6] [7], 2.8% in Canada [8], 3.1% in Brazil [9], 3.3% in Nigeria [10], to 4.1% in Egypt [11].…”
Section: Introductionmentioning
confidence: 99%
“…This was found to be same as seen by another national study by Majeed et al 6 where he showed that 24% babies whose mother had PROM, developed birth asphyxia. PROM is not only associated with increased incidence of emergency caesarian section but it is also associated with birth asphyxia but the frequency of birth asphyxia in PROM was found to be higher as compared to international studies (24.9% vs. 10%) 15 .…”
Section: Discussionmentioning
confidence: 62%
“…Complications such as respiratory distress syndrome (RDS), intraventricular hemorrhage (IVH) and necrotizing enterocolitis (NEC) contribute to most of the cases of neonatal mortality. 11,12 PROM and PPROM are commonly seen in the obstetric ward in our country. There are very limited studies about PPROM.…”
Section: Introductionmentioning
confidence: 84%